The Importance of Task-Based Learning and Focus on Form in Teaching Phraseology - Chrissou, Marios (Kalbotyra, 2020)
A controversial issue for teachers of German as a foreign language is the balance between content and form. This also applies to vocabulary work in the field of phraseology. The modeling of language competence in the communicative approach is based on the understanding of language as a means of communication. Accordingly, the primary claim of communicative language didactics is to go beyond the description of structures of the foreign language and to place appropriate, situated linguistic action at the center of teaching. Against this theoretical background, content-oriented approaches such as Task-Based Learning have emerged in foreign language didactics, which emphasize the communicative aspect of language and place the didactic emphasis on situated, authentic tasks. Nevertheless, this emphasis did not lead to the suppression of form-based approaches which consider precision in language mastery by focusing on formal aspects through exercises to be necessary and desirable.This paper examines the question of the importance of exercises and tasks in phraseology-based vocabulary work. Against the theoretical background of the approaches of Task-Based Learning (TBL) and Focus on Form (FoF), possibilities for the integration of content-oriented and form-focussing teaching concepts for the promotion of phraseological competence are shown by means of concrete examples. Furthermore, the question of their balance in teaching is discussed.
Keywords: phraseology; phrasemes; vocabulary work; task based learning; focus on form